2015
DOI: 10.1002/ejlt.201400431
|View full text |Cite
|
Sign up to set email alerts
|

Lecithin and parabens play a crucial role in tripalmitin‐based lipid nanoparticle stabilization throughout moist heat sterilization and freeze‐drying

Abstract: The administration of Lipid nanoparticles (LNP) by different routes involves technological challenges, particularly those associated to sterilization and stability. Publications suggest the stability of LNP formulations throughout harsh production conditions involved in pharmaceutical procedures is highly dependent on the type of surfactant used. Therefore, the capacity of tripalmitin-based LNP to withstand moist heat sterilization and freeze -drying has been evaluated using poly(vinyl alcohol), soya lecithin,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(11 citation statements)
references
References 42 publications
0
11
0
Order By: Relevance
“…In vitro stability in SGF and SIF confirmed that particle size of formulations were found in nano-ranges in gastric fluid due to effectiveness of polymeric coating (EL100) and almost maintained in the basic environment of the intestinal fluid till their arrival and maintained positivity in terms of particle size. In the literature, it was described that SLN stability can be improved by polymer coating [2830].…”
Section: Resultsmentioning
confidence: 99%
“…In vitro stability in SGF and SIF confirmed that particle size of formulations were found in nano-ranges in gastric fluid due to effectiveness of polymeric coating (EL100) and almost maintained in the basic environment of the intestinal fluid till their arrival and maintained positivity in terms of particle size. In the literature, it was described that SLN stability can be improved by polymer coating [2830].…”
Section: Resultsmentioning
confidence: 99%
“…The positive influence of lecithin in improving the stability of SLN formulations in terms of particle size and PI has been described in the literature [41,27,29]. This amphiphilic substance Table 2 Effect of GLI incorporation (1 mg) on mean particle size, PI, zeta potential (f) and drug entrapment (EE%), of Precirol-based SLN freshly prepared and after one month storage at 5 ± 3°C (mean ± SD, n = 3).…”
Section: Improvement Of Sln Stability In Gastrointestinal (Gi) Conditmentioning
confidence: 89%
“…While planning the functionalization of nanoparticles, it is important to consider different factors such as (i) particle size, (ii) surface charge, (iii) hydrophobicity, (iv) target cells, and (v) administration route among other relevant parameters. As an example, it is known that positively charged nanoparticles are preferentially taken up by cells and by this, coating of nanoparticles with molecules with positive charge has become a commonly used strategy to enhance cellular uptake [ 101 , 105 , 106 , 107 ]. As referenced to before, hydrophobicity is especially important when using an intravenous administration route due to opsonization of nanoparticles by macrophages.…”
Section: Preparation Methods and Functionalization Approachesmentioning
confidence: 99%